Without Neutrality: The Potential of Critical Librarianship - Jaeger-McEnroe, Emily (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire)

(untitled) (Canadian Association of Professional Academic Librarians / Association Canadienne des Bibliothécaires en Enseignement Supérieur, 2025)
Neutrality is often treated as a foundational value of librarianship, but its adoption was neither inevitable nor apolitical. This paper traces the historical development of neutrality within the profession, showing how it emerged in response to external political pressures during World War II and the Cold War. Once codified, neutrality hindered further development of the profession, particularly in matters of social responsibility or justice. Critical librarianship is a librarianship that did not stop changing after the contingent addition of neutrality as a library value. This paper argues that the many disparate fights of critical librarianship are united by a shared rejection of the neutrality doctrine that has pervaded mainstream librarianship. Without neutrality, critical librarianship would not be a separate movement—it would simply be librarianship.